HUBUNGAN KONSUMSI BUAH DAN SAYUR, POLA MAKAN, DAN AKTIVITAS FISIK DENGAN KEJADIAN GIZI LEBIH PADA PENGENDARA OJEK ONLINE DI SHELTER STASIUN DEPOK BARU - Annisa Safitri (2023)
The online motorcycle taxi drivers have high mobility, spending most of their time on the road, which can affect their food intake and physical activity, leading to the occurrence of overnutrition. The purpose to investigate the relationship between fruit and vegetable consumption, eating patterns, and physical activity with the occurrence of overnutrition among online motorcycle taxi drivers at the Shelter Stasiun Depok Baru. This study is an analytical observational research with a cross-sectional design approach. The study population consists of 75 online motorcycle taxi drivers at Shelter Stasiun Depok Baru. The sample for this study was selected using purposive sampling technique. Data was collected through measurements of body weight and height, SQ-FFQ, and Baecke physical activity scale questionnaire. The statistical test used Chi-Square test. The results of the statistical test showed that there is a significant relationship between overnutrition and vegetable consumption (p = 0.005), eating patterns (p = 0.009), and physical activity (p = 0.002) among online motorcycle taxi drivers at Shelter Stasiun Depok Baru. However, there is no significant relationship between overnutrition and fruit consumption (p = 0.385). Increase their fruit and vegetable intake, maintain a healthy eating pattern, and engage in physical activities to support achieving optimal nutritional status among online motorcycle taxi drivers